ANTICANCER ACTIVITY OF CAMELLIA SINENSIS MEDIATED COPPER NANOPARTICLES AGAINST HT-29, MCF-7 AND MOLT-4 HUMAN CANCER CELL LINES - MENDHULKAR VIJAY D; YADAV ANU (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: With the advancement in nanotechnology, it is imperative to unearth its applications in medicine. Present investigation deals with the copper nanoparticles biosynthesizing capability of the leaves of medicinally important plant,Â Camellia sinensis. Methods: The phytosynthesized CuNPs were characterized by EDX, NTA, XRD, SEM, TEM and FTIR analysis. In the current study, we have made attempts to exploit the anticancer ability of the copper nanoparticles against HT-29 colon cancer, MCF 7 breast cancer and MOLT-4 leukemia cancer cell lines via SRB assay. We also carried out the synergistic activity with standard drug Adriamycin (ADR). Results: The synthesis of CuNPs was confirmed using EDX analysis where the presence of a strong optical absorption peak was observed at 1 keV, which is typical for the absorption of metallic copper nanoparticles. According to the results obtained, CuNPs showed good antiproliferative results in a dose dependant manner on HT-29 and MCF-7 cell lines, with 80 Âµg/ml concentration giving the best result. The synergistic effect of CuNPs+ADR was even better than that of CuNPs alone on all the cell lines. The synergism drug combinations showed highly responsive results on the leukemia cell line compared to individual drugs. Conclusion: Among all the treatments and cell lines studied, the most favorable and responsive antiproliferative impact was recorded for CuNPs+ADR combination treatment at 40Âµg/ml concentration on MCF-7 breast cancer cell line. Keywords: CuNPs, Camellia sinensis, Anticancer, Sulforhodamine B assay, HT-29, MCF-7, MOLT-4.